Analisis Sikap Peduli Lingkungan Siswa Melalui Program Adiwiyata di UPT SD Inpres Bisara - Musdalifa Musdalifa; Nasrah Nasrah; Anisa Anisa (Journal on Education, 2024)
This type of research is qualitative with descriptive methods. This research aims to analyze students' environmental care attitudes through the Adiwiyata program. The population used was all UPT SD Inpres Bisara students. The sampling technique used in this research was a random sampling technique in which a sample of 58 people were randomly obtained from classes IV, V, and VI. Data collection techniques consist of questionnaire sheets, interview sheets, observation sheets and documentation sheets. Data validity testing consists of extended observations, conducting member checks, using reference materials. Data analysis techniques consist of data collection, data reduction, data presentation and drawing conclusions and verification. Research procedures consisting of research planning, data collection, data analysis and interpretation and presentation of results. Based on the research results, it can be concluded that students' attitudes towards the environment are quite good, with 72.414% of students' behavior showing a high level of concern for the school environment.